Estimation of the Lifetime Quality-Adjusted Life Years (QALYs) Lost Due to Syphilis Acquired in the United States in 2018. (10th June 2022) - Lee, Kyueun; You, Shiying; Li, Yunfei; Chesson, Harrell; Gift, Thomas L; Berruti, Andrés A; Hsu, Katherine; Yaesoubi, Reza; Salomon, Joshua A; Rönn, Minttu
Abstract: Background: The purpose of this study was to estimate the health impact of syphilis in the United States in terms of the number of quality-adjusted life years (QALYs) lost attributable to infections in 2018. Methods: We developed a Markov model that simulates the natural history and management of syphilis. The model was parameterized by sex and sexual orientation (women who have sex with men, men who have sex with women [MSW], and men who have sex with men [MSM]), and by age at primary infection. We developed a separate decision tree model to quantify health losses due to congenital syphilis. We estimated the average lifetime number of QALYs lost per infection, and the total expected lifetime number of QALYs lost due to syphilis acquired in 2018. Results: We estimated the average number of discounted lifetime QALYs lost per infection as 0.09 (95% uncertainty interval [UI] .03–.19). The total expected number of QALYs lost due to syphilis acquired in 2018 was 13 349 (5071–31 360). Although per-case loss was the lowest among MSM (0.06), MSM accounted for 47.7% of the overall burden. For each case of congenital syphilis, we estimated 1.79 (1.43–2.16) and 0.06 (.01–.14) QALYs lost in the child and the mother, respectively. We projected 2332 (1871–28 250) and 79 (17–177) QALYs lost for children and mothers, respectively, due to congenital syphilis in 2018. Conclusions: Syphilis causes substantial health losses in adults and children. Quantifying these health losses in terms of QALYs can inform cost-effectiveness analyses and can facilitate comparisons of the burden of syphilis to that of other diseases. Abstract : Our study showed that syphilis causes substantial health losses in both adults and children in the United States. Expanding syphilis screening and access to antenatal care can prevent sequelae and thereby reduce the impact of syphilis on quality of life.